Reflections about the community-based tourism and indigenous peoples in light of the Pataxó case (Bahia, Brazil) - Neves, Sandro Campos (Revista Turismo em Análise, 2021)
This work discusses aspects of the Brazilian development model of community-based tourism (CBT) in light of the case of the Pataxó indigenous people from the village of Coroa Vermelha in the municipality of Santa Cruz Cabrália, state of Bahia (Brazil). It portrays the ways in which the basic theoretical principles of CBT are configured in the Pataxó empirical reality, seeking to rethink practical aspects of its application. The ethnographic research undertaken among the Pataxó is the backdrop for the reflection and the analysis of public documents on CTB in Brazil. It concludes that the basic principles of the CTB – community self-management, solidary economic principles, and preservation of the community cultural heritage – are quite different in the Pataxó reality from those foreseen and proposed in the model. Thus, it proposes elements for an assessment on the principles of CTB and its application models so that they become closer to the needs expressed by the field study of indigenous communities and the others to which the model applies.